Scenario-guided policy analysis workshop - Entebbe, Uganda - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Regional stakeholders from governments, development organizations, civil society and academia came together from 25 to 27 June in Entebbe, Uganda for a workshop that focused on scenario-guided policy analysis on the future of development, food security and the environment under climate change in East Africa. The workshop was organized by UNEP WCMC, CCAFS and The ARCOS Network and is part of UNEP WCMC’s project Commodities and Biodiversity, Planning for Future Capacity funded by The MacArthur Foundation. Photos: E. van de Grift.